2011
DOI: 10.1002/rcm.4907
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter flow in the food web at a temperate heath under multifactorial climate change

Abstract: The rising atmospheric CO(2) concentration, increasing temperature and changed patterns of precipitation currently expose terrestrial ecosystems to altered environmental conditions. This may affect belowground nutrient cycling through its intimate relationship with the belowground decomposers. Three climate change factors (elevated CO(2), increased temperature and drought) were investigated in a full factorial field experiment at a temperate heathland location. The combined effect of biotic and abiotic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 92 publications
4
14
0
Order By: Relevance
“…Moreover, Arndal et al [48] reported that Deschampsia root biomass in the same experimental plots as examined here had increased after about three years of treatment, whereas root N-content decreased under elevated CO 2 , which could also contribute to a decreased relative N-content of enchytraeids feeding partially on roots. Taken together, our observations on enchytraeids after one and two [25,43] versus seven and eight years (present study) of treatment point in the direction that elevated CO 2 can have rather immediate positive effects on root biomass and perhaps exudation fuelling microbial growth e.g. Ref.…”
Section: Sampling 12 August 2012supporting
confidence: 70%
See 1 more Smart Citation
“…Moreover, Arndal et al [48] reported that Deschampsia root biomass in the same experimental plots as examined here had increased after about three years of treatment, whereas root N-content decreased under elevated CO 2 , which could also contribute to a decreased relative N-content of enchytraeids feeding partially on roots. Taken together, our observations on enchytraeids after one and two [25,43] versus seven and eight years (present study) of treatment point in the direction that elevated CO 2 can have rather immediate positive effects on root biomass and perhaps exudation fuelling microbial growth e.g. Ref.…”
Section: Sampling 12 August 2012supporting
confidence: 70%
“…In a previous study of enchytraeids at the CLIMAITE experiment we observed that increased CO 2 had a positive effect on enchytraeid biomass after two years of treatment [25,43]. However, in 2012e2013 the positive effect of CO 2 was not there anymore for any of the enchytraeid species, nor the entire enchytraeid community.…”
Section: Sampling 12 August 2012mentioning
confidence: 70%
“…We note that drought intensity did not have direct influence on biodiversity when assessed months after the end of dry conditions, whereas we did observe an effect of mean annual soil water content on the diversity of collembolans. Our previous studies have shown that drought can cause substantial and acute negative effects on abundance of nematodes, collembolans and enchytraeids in our study area and similar ecosystems25364647. Biomass of enchytraeids, as determined shortly after experimental drought episodes, was reduced when water content (0–20 cm depth) was approaching 5 volume %, but the population recovered within months after the soil water content was restored253648.…”
Section: Discussionmentioning
confidence: 60%
“…belowground plant inputs form the dominant C resource and determine soil food web structure (Kuzyakov and Domanski 2000;Eissfeller et al 2013). For example, in temperate forests and grasslands, soil arthropods have been found to predominantly rely on root-rather than leaf litterderived C (Andresen et al 2011;Pollierer et al 2012). Surprisingly, although approximately 40 % of the global ice-free land surface is currently used for agricultural production, little is known on the importance of below-versus aboveground resources for soil arthropod communities in arable systems.…”
Section: S Scheu and O Butenschoen Contributed Equallymentioning
confidence: 99%